The social and psychological effects of women committing a crime and entering prison (a theoretical social study) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The prison sentence has a great impact on the female prisoner (inmate), and this punishment raises many aspects and effects that should be paid attention to and deeply studied, especially in light of the high rates of crimes in general, and women’s crimes in particular. There is no doubt that women fall into Delinquency, crime and imprisonment as a punishment for this act that opposes the values ​​and principles of society have great effects on the imprisoned woman from various psychological and social aspects. An element in it, which is the woman, the mother, the educator, the role model, and the main element in raising children, caring for them, and caring for them. The research will deal with the social and psychological effects of the woman entering prison, in addition to researching the reasons leading to her committing the crime and entering this closed place. It would mitigate and help address the causes that led to this behavior, and mitigate as much as possible the impact of women entering prison on the individual and society alike.